PELATIHAN MANAJEMEN PEMASARAN INDUSTRI RUMAH TANGGA RAKET TENIS MEJA - Tri Yulistyawati Evelina; Shinta Maharani Trievena; Ahmad Fauzi; Ayu Sulasari (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
The purpose of this service activity is to provide knowledge and skills for household members in managing Marketing Management. PKM methods adopted to overcome problems, namely: Pre Training, Design Training and Implementation of training The results of this service are expected to be an increase in knowledge and skills of Marketing Management and Online-Based Marketing Management and Marketing Management assistance for household members of the Malang City Table Tennis Racket Household Industry.